Molecular docking and molecular dynamic simulation studies to identify potential terpenes against Internalin A protein of Listeria monocytogenes - K, Deepasree; Venugopal, Subhashree (Frontiers in Bioinformatics, 2024)
IntroductionEver since the outbreak of listeriosis and other related illnesses caused by the dreadful pathogen Listeria monocytogenes, the lives of immunocompromised individuals have been at risk.Objectives and MethodsThe main goal of this study is to comprehend the potential of terpenes, a major class of secondary metabolites in inhibiting one of the disease-causing protein Internalin A (InlA) of the pathogen via in silico approaches.ResultsThe best binding affinity value of −9.5 kcal/mol was observed for Bipinnatin and Epispongiadiol according to the molecular docking studies. The compounds were further subjected to ADMET and biological activity estimation which confirmed their good pharmacokinetic properties and antibacterial activity.DiscussionMolecular dynamic simulation for a timescale of 100 ns finally revealed Epispongiadiol to be a promising drug-like compound that could possibly pave the way to the treatment of this disease.